The policy dystopia model adapted to the food industry: the example of the Nutri-Score saga in France - Mialon, Melissa (My University, 2018)
In October 2017 in France, the government recognized the Nutri-Score front-of-pack labelling system as the only official system to be used on food products. As of July 2018, a total of 70 companies had implemented it voluntarily. There is ample evidence to support its use, and multiple expected benefits in terms of public health. We present here an essay discussing about the Nutri-Score saga. A policy dystopia model, from the literature on tobacco industry tactics, was adapted to classify the corporate political activity of the food industry during the development and implementation of the Nutri-Score. We conclude that, despite public commitments made by some industry actors to implement this system, the food industry is still strongly trying to influence policy and public opinion in the country. There are and will be many hurdles along the way, with food industry members trying to influence regulation at the European level, and building alliances with the media, among others, in France. Hopefully, public health objectives will prevail over commercial interests, in France and abroad.
Keywords: Corporate political activity; Front-of-pack labelling; Food industry; Public policy; Public health; Cancer; Smart & Sustainable Planet